The Study of Aesthetic Features Interpretation and Cultural Identity of Baiku Yao Dress Patterns - Bai, Ge; Ruangchewin, Puvasa (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2023)
The objective of this research is to design the Baiku Yao Dress Culture Learning Center in Huaili Village and to select 6 interviewees using a heterogeneous sampling method. The majority of them have been dressed in Baikuyao national costumes for more than three months and can provide the interviewer with the necessary information. Semi-structured interviews, literature analysis, and participant observation were all used in this study. Thematic analysis was used to examine the data. The national memory of Baiku Yao created the aesthetic characteristics of this ethnic group during the formation of Baiku Yao dress art; the national memory of Baiku Yao is embodied in the aesthetic characteristics of costumes aesthetic feeling, which explains the cultural identity of Baiku Yao dress. The findings reveal the following four scenarios: First, a look at the historical development of Baiku Yao dress patterns. The aesthetic composition and cultural significance of Baiku Yao dress patterns are discussed in the second part. Third, the identification of Baiku Yao dress patterns and cultural changes. Fourth, the "Huaili Village Cultural Learning Center" capitalizes on the ability of Huaili Village residents to inherit active communication community culture through education, training, and exhibitions, and gives learners full play.